Some Physical Properties and Erosion Behaviour of Kanpur Alluvial Soils - Chandra, Subhash; De, S.K. (Journal of Soil and Water Conservation, 2022)
It has been frequently observed that soils under similar conditions of climate, topography and vegetative covering, differ mutually in the extent of their erosion. Such differences may be attributed to the physical makeup of soil. The physical properties of soils or sub-soils are not easily modified. Consequen- tly, such factors as soil texture, bulk density, water holding capacity, permeability to water, pore space, and aggregation etc. are frequently more important than chemical data in deter- mining the potential possibilities of land. A study was, therefore, undertaken on the physical characteristics of the important soil types of the Gangetic alluvium in the central region of the State. This could be of importance in studying the behaviour of soil towards fertilization, irrigation and other soil conservation practices.